Frontiers in clinical drug research. - Rahman, Atta-ur-, 1942- (Frontiers in Clinical Drug Research - Central Nervous System., 2013)
This ebook series. It covers a range of topics such as the development and pathophysiology of the brain and spinal cord, physiological sites of drug action in the CNS and clinical findings on drugs used to treat CNS defects due to injury or impaired development. In addition to clinical research on humans, the book also highlights other avenues of CNS medicine and research such as pain medicine, stem cell research, pharmacology, toxicology and translational models in animals.